MEMBANGUN PERADABAN MUSLIM STUDI ATAS PEMIKIRAN PENDIDIKAN ISLAM MUHAMMAD QUTHB - Murjani Murjani (Cross-border, 2022)
Muhammad Qutb is a prominent Muslim thinker who seeks to objectively see the socio-religious and social conditions of Muslims, especially in Egypt. According to MQ, the marginalization faced by Muslims is due to the fact that these people only use the Koran as reading without discussing and implementing its teachings. In addition, Muslims also put aside the deeds of faith which actually stems from their theological errors. The theological paradigm should change from ghairu qabilin li al-niqas to thinking that is "on going process" and "on going formation". Rooted faith will become energy that gives birth to a steady heart, soul and living emotions.